Analisa Keterdapatan Batugamping Menggunakan Metode Resistivitas Pada Blok A Area Penambangan PT Graha Batu Perdana Kecamatan Bungku Pesisir Kabupaten Morowali - Tesalonika Mangnga Tolan; Jahidin Jahidin; Erzam Salahudin Hasan (Program Studi Teknik Geofisika FITK UHO, 2023)
This research was conducted to determine the resistivity values and the presence of limestone in Block A of PT Graha Batu Perdana mining area, Bungku Pesisir Subdistrict, Morowali Regency, using the Wenner-Schlumberger resistivity method. This study utilized secondary data and falls under the category of data processing studies, with measurements conducted along 4 traverses, each with a length of 310 m. The data obtained consisted of potential difference values and current strength, which were then processed using Microsoft Excel to obtain resistivity values. Subsequently, a 2D processing was carried out using res2Dinv to generate a 2D cross-section, which was then interpreted to identify subsurface conditions based on resistivity values. The distribution of limestone in the research area along 4 traverses is as follows traverse 1 had a resistivity value of 694 Ωm with a thickness of 30,14 m, traverse 2 had resistivity values ranging from 1089 to 2350 Ωm with thinknesses between 28,15 and 43,14 m, traverse 3 had resistivity values ranging from 544 to 15108 Ωm with thinknesses between 1,25 and 39,4 m, traverse 4 had resistivity values ranging from 710 to 3325 Ωm with thinknesses between 38,15 m.